HUBUNGAN ANTARA PENGETAHUAN PELESTARIAN LINGKUNGAN DAN INTENSI SISWA TERHADAP OUTPUT SEKOLAH DENGAN PARTISIPASI SISWA DALAM KEBERSIHAN LINGKUNGAN - Suhardjo Suhardjo (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2016)
The objective of this research is to analuyze the relationship of knowledge and enviromental conservation intention output of school students with students participation in the clean enviroment. The methode used was a survey and correlational techniques in One Senior High School, Depok.. The sampel of this research were 70 students wich proporsional random sampling. The results showed as follow: (1) The relationship between the Environmental Protection Knowledge with Students Participation in Environmental Hygiene showed a negative relationship. (2) The relationship between the intentions of the Output School Students with Student Participation in Environmental Hygiene showed a positive relationship. (3) The relationship between knowledge and intention of Environmental Protection against Output School Students together with Student Participation in Environmental Hygiene showed a positive relationship. From the research, the conclusion is that most of the students were able to understand the concepts, facts and procedures related to conservation of the environment, so most students have a strong intention to academic and non-academic.